Tarif Pajak, Sunset Clause, Peredaran Bruto, Kemanfaatan NPWP dan Kepatuhan Wajib Pajak - Pradnyani, Desak Kade Bunga Ayu; Noviari, Naniek (E-Jurnal Akuntansi; Vol 31 No 10 (2021)DO - 10.24843/EJA.2021.v31.i10.p18, 2021)
MSME taxpayer compliance is still low, especially the compliance of taxpayers registered at the Tabanan Pratama Tax Service Office 2015-2020. This is reflected in the number of taxpayers who submit annual tax returns that are not proportional to the number of registered taxpayers. The purpose of this study was to examine the effect of tax rates, sunset clause, gross circulation, and the benefits of Taxpayer Identification Numbers (TIN) on MSME taxpayer compliance. The number of samples used was 100 using accidental sampling. Data collection was carried out through interviews and questionnaires. The analysis technique used in this research is multiple linear regression analysis.  The results showed that the tax rate, sunset clause, gross circulation, and TIN benefits had a positive effect on MSME taxpayer compliance. Keywords: Tax Rates; Sunset Clause; Gross Circulation; TIN Benefits; Taxpayer Compliance.